Mempertimbangkan Hermeneutika sebagai Metode Tafsir Al-Qur’an - Asep Shodiq Maulana (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2009)
Da’wah as process of actualizing Islamic message in the  real life context in turn will weigh of grasp position to Al Qur'an text. Islamic massage is sent away  dialoguable  with various social's environmental condition. In this condition it is needed one of relevant methodology in understanding Al-Qur’an.  The methodology is a method can catch meaning of text that can't only by rely grasp of language grammar corner only, but also social's context grasp of that text. That method is named hermeneutika.